Evidence submitted to the House of Commons-Environment, Food and Rural Affairs Committee’s Inquiry on Rural Broadband and Digital Only Services, published on 26 June 2019 - Fuchs, Christian; Michalis, Maria

Slow Media: How to Renew Debate in the Age of Digital Authoritarianism - Fuchs, Christian (The Conversation)

Henry A. Giroux and the Culture of Neoliberal Fascism - Fuchs, Christian (Los Angeles Review of Books)

Herbert Marcuse: Einige gesellschaftliche Folgen moderner Technologie - Fuchs, Christian (Zeitschrift für Didaktik der Philosophie und Ethik)

Anisotropic Water-Mediated Proton Conductivity in Large Iron(II) Metal–Organic Framework Single Crystals for Proton-Exchange Membrane Fuel Cells - Bunzen, Hana; Javed, Ali; Klawinski, Danielle; Lamp, Anton; Grzywa, Maciej; Kalytta-Mewes, Andreas; Tiemann, Michael; von Nidda, Hans-Albrecht Krug; Wagner, Thorsten; Volkmer, Dirk (ACS Applied Nano Materials)
Herein we present a new proton-conducting iron(II) metal–organic framework (MOF) of an unusual structure formed by chains of alternating bistriazolate-p-benzoquinone anions and iron(II) cations with four axially coordinated water molecules. These chains assemble via π–π stacking between the aromatic units to form a three-dimensional grid-like network with channel pores filled with water molecules. The material was structurally characterized by single-crystal XRD analysis, and its water and thermal stability was investigated. The proton conductivity was studied by impedance measurements on needle-like single crystals. A simple but efficient measurement setup consisting of interdigital electrodes was used. The influence of the crystal orientation, temperature, and humidity was investigated. The iron(II)-MOF showed the highest proton conductivity of 3.3·10–3 S cm–1 at 22 °C and 94% relative humidity. Contrary to most known structures, the conductivity in this material is controlled by chemical properties of the pore system rather than by grain boundaries. The presented material is the starting point for further tailoring the proton-conducting properties, independent of morphological features which could find potential applications as membrane materials in proton-exchange membrane fuel cells.

Copper Oxide/Silica Nanocomposites for Selective and Stable H2S Gas Detection - Paul, Andrej; Weinberger, Christian; Tiemann, Michael; Wagner, Thorsten (ACS Applied Nano Materials)
A composite material of copper oxide (CuO) dispersed in the nanopores of KIT-6 silica (SiO2) is used as a dosimetric sensor for the detection of hydrogen sulfide (H2S) gas in low parts per milion concentrations. The sensor principle is based on the reversible chemical conversion of CuO to CuS, which guarantees a high selectivity, and on the corresponding percolation-induced change in electronic conductance.

Sono una madre single. Non sento di poter essere competitiva quanto altri: esperienze di personale precario nelle università del Regno Unito. Translated by Gloria Dagnin - Allmer, Thomas (Studies in Communication Sciences)

Joining of blanks by cold pressure welding: Incremental rolling and strategies for surface activation and heat treatment - Schmidt, H.C.; Homberg, W.; Orive, A.G.; Grundmeier, G.; Duderija, B.; Hordych, I.; Herbst, S.; Nürnberger, F.; Maier, H.J. (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

The Human is Dead, Long Live the Algorithm!. Human-Algorithmic Ensembles and Liberal Subjectivity - Matzner, Tobias (Theory, Culture & Society)
The article analyzes the relation of humans and technology concerning so called ‘intelligent’ or ‘autonomous’ algorithms that are applied in everyday contexts but are far removed from any form of substantial artificial intelligence. In particular, the use of algorithms in surveillance and in architecture is discussed. These examples are structured by a particular combination of continuity and difference between humans and technology. The article provides a detailed analysis of boundary practices that establish continuity and oppositions between humans and information technology, referring to their exemplary depiction in movies. Both strands of boundary practices have the potential to challenge as well as sustain the position of the human as liberal, autonomous subject. Finally, it is shown how the particular combination of continuity and difference that structures the use of algorithms maintains the power of liberal, autonomous subject positions, while the shift of decisions to the algorithms seems to decenter the human.

Privacy - Matzner, Tobias; Ochs, Carsten (Internet Policy Review)

Mediale und soziale Bedingtheit der Subjekte des Privaten – ein Versuch mit Hannah Arendt - Matzner, Tobias (Privatsphäre 4.0. Eine Neuverortung des Privaten im Zeitalter der Digitalisierung)

Organic Self-Adaptable Real-Time Applications - Khaluf, Lial; Rammig, Franz-Josef

History and Aesthetics of Progress Indicators [Edistymispalkkien historia ja estetiikka] - Raczkowski, Felix; Shnayien, Marie-Luise (Tekniikan Waiheita)

Zwei Betrachtungen von Sicherheit und Privatheit nach Snowden - Auerbach, Benedikt; Shnayien, Marie-Luise; Kiltz, Eike; Tuschling, Anna (Datenschutz und Datensicherheit - DuD 43)

Determinant groups of Hermitian lattices over local fields - Kirschmer, Markus (Archiv der Mathematik)
We describe the determinants of the automorphism groups of Hermitian lattices over local fields. Using a result of G. Shimura, this yields an explicit method to compute the special genera in a given genus of Hermitian lattices over a number field.
Keywords: General Mathematics

Jesus-Transformation als Filmmusikkinderbibel. Mario Castelnuovo-Tedescos Klavierzyklus „Εὐαγγέλιον. La storia di Gesù, narrata ai Fanciulli in 28 piccoli pezzi per Piano“ (1949) - Schroeter-Wittke, Harald (Jesus-Transformationen)

Gott lässt sich nicht spotten! (Gal 6,7) Blasphemie als theologisches, strafrechtliches und (religions-)pädagogisches Thema. Eine evangelische Position - Schroeter-Wittke, Harald (Staat und Religion. Aspekte einer sensiblen Verhältnisbestimmung)

Vertrauens-Bildung in evangelische Übergänglichkeit. Eine Einführung in Gemeindekultur- und -medienpädagogik - Schroeter-Wittke, Harald; Fermor, Gotthard (Gemeindepädagogik)

David Danced. Musikalische Spurensuche zu einer populären Szene - Schroeter-Wittke, Harald (Davidfigur und Opfermotiv. Jüdisch-christliche Transformationen)

8. Sonntag nach Trinitatis (11.8.2019). Jes 2,1-5: Auf geht’s – Von Sehnsuchtsliedern und Rückenwind - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

Jubilate (3. Sonntag nach Ostern) 12.05.2019. Sprüche 8,22-36: Ein Lustspiel als Grammatik des Lebens - Schroeter-Wittke, Harald; Kirsner, Inge (Predigtstudien I/2)

Kleinkinder und Medien in Deutschland: Eine kultursensible Studie zur (Re-)Konstruktion mediatisierter Kultur- und Sozialisationskontexte in der Frühen Bildung - Günesli, Habib
Dieses Promotionsvorhaben zentriert die Frühe (Medien-)Bildung sowie die Forschungs- und Themengebiete Migration und Interkulturalität, die in der Kindheitsforschung generell und kulturvergleichenden Kindheitsforschung speziell bislang nicht hinreichend berücksichtigt wurden. Der Fokus der vorliegenden Qualifikationsarbeit, die im Rahmen des interventiv angelegten, in Dortmund angesiedelten, Forschungsprojekts KidSmart – Medienkompetent zum Schulübergang (2010-2012) entstanden ist (vgl. Marci-Boehncke/Rath 2013), liegt daher auf den jenseits quantitativer Nutzungsstudien (vgl. z.B. mpfs 2015; 2013) verhältnismäßig gering beachteten Lebens- und Medienwelten von Vorschulkindern in Abhängigkeit von ihrer familiär praktizierten Herkunftskultur bzw. einer mehrkulturellen (Medien-)Sozialisation. Mit dieser Qualifikationsarbeit wurde das Ziel verfolgt, unter kultursensitiver und intersektionaler Perspektive, in einem multiperspektivischen und multimethodischen Design sowohl empirisch-quantitative als auch empirisch-qualitative Daten zu erfassen und so die (Medien-)Sozialisationskontexte von unterschiedlich (herkunfts-)kulturell geprägten, speziell deutsch-türkischen und deutschen, vier und fünf Jahre alten Kindern, mit Bezug auf die sozialen Felder Familie und Kita, möglichst unverfälscht, also am gemeinten Sinn sozialen Handelns, zu (re-)konstruieren. Ziel ist es, bildungsbiographisch bedingte und als ungünstig verstandene Lebenslagen, Lebensphasen und Lebensweisen möglichst früh zu erkennen und auf diese im Verbund, im Sinne der Educational Governance (vgl. Marci-Boehncke/Rath 2013; Heimbach- Steins/Kruip 2011), zu reagieren, um Kindern in Sachen Bildungs- und Teilhabechancen generell und Mediennutzung und Medienkompetenzvermittlung speziell möglichst günstige „Ausgangsbedingungen zum Schuleintritt [...] zu ermöglichen“ (Marci- Boehncke/Weise 2007, 45) – und zwar über alle sozialen ungleichheitsdimensionellen Prägungen hinweg. Um bestehende Kenntnislücken und Spekulationen, die beim erzieherischen Personal nachweislich bestehen, schließen zu können, sollte ein Zugang zu den gegenwärtig konkreten lebens- und medienweltbezogenen Wirklichkeiten der untersuchten Kinder ermöglicht werden. Entsprechend erfolgte die Konzeption dieses (Teil-)Projekts vor dem Hintergrund der Habitus- und Kapitalsortentheorie von Bourdieu (1987; 1986; 1983). Als Methode der quantitativen Datengewinnung wurden halbstandardisierte Fragebögen gewählt, die den Eltern und Erzieher_innen zu Beginn und mit Abschluss der Projektdurchführung für die Bearbeitung zur Verfügung gestellt und mit Hilfe der Fragebogen-Software GrafStat erfasst und ausgewertet wurden. Das qualitative Datenmaterial, das während der Projektdurchführung mittels der Puppet-Interview- Methode (vgl. Weise 2008; Paus-Hasebrink 2005) gewonnen werden konnte, wurde vor dem Hintergrund der Grounded Theory und mittels der Daten- und Analysesoftware MaxQDA ausgewertet (vgl. Strübing 2011; Glaser/Strauss 2005). Auf der Grundlage der Heuristischen Sozialforschung (vgl. Kleining 1995) wurde auf Methoden- und Datenebene dieses Vorhabens ein komplexes, trianguliertes Forschungsdesign eingesetzt (vgl. Flick 2011).
Keywords: Frühe Kindheit; Frühe Medienbildung; Bildungsgerechtigkeit; Kultursensitivität; Inklusion; Intersektionalität

"iphone Abi" - Erfahrungen eines deutsch-türkisch geprägten Kleinkindes mit Medien im Enkulturationsprozess (Medien: Wissen - Können - Wollen: Medienbildung, Medienkritik, Partizipation, Digitalität, Ethik. Festzeitschrit zu Ehren von Professor Dr. Dr. Matthias Rath)
Habib Güneşli diskutiert in seinem Artikel die Wortschöpfung iPhone Abi, die ein deutsch-türkischer Junge nutzt, um sich sprachlich im multikulturellen Raum zu orientieren.

Experimental Reconstruction of Entanglement Quasiprobabilities - Sperling, Jan; Meyer-Scott, E.; Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine (Physical Review Letters)

Subcycle Wannier-Stark Localization by Mid-Infrared Bias in Gallium Arsenide - Meier, Torsten; Bühler, Johannes; Schmidt, Christian; Heinrich, Alexander-Cornelius; Allerbeck, Jonas; Podzimski, Reinold; Berghoff, Daniel; Schmidt, Wolf Gero; Reichl, Christian; Wegscheider, Werner; Brida, Daniele; Leitenstorfer, Alfred (XXI International Conference on Ultrafast Phenomena 2018 (UP 2018))
The fundamental interband absorption in gallium arsenide shows a strong blue shift when biased by mid-infrared transients exceeding 10 MV/cm. This subcycle feature is induced by the localization of electronic wavefunctions from 3D to 2D.

Spatially asymmetric transients of propagating exciton-polariton modes in a planar CdZnTe/CdMgTe guiding structure - Vondran, J.; Spitzer, F.; Bayer, M.; Akimov, I. A.; Trautmann, Alexander; Reichelt, Matthias; Meier, Cedrik; Weber, N.; Meier, Torsten; André, R.; Mariette, H. (Physical Review B)

Generating two-mode squeezing with multimode measurement-induced nonlinearity - Riabinin, Matvei; Sharapova, Polina; Bartley, Tim; Meier, Torsten (arXiv:1912.09097)
Measurement-induced nonclassical effects in a two-mode interferometer are investigated theoretically using numerical simulations and analytical results. We demonstrate that for certain parameters measurements within the interferometer lead to the occurrence of two-mode squeezing. The results strongly depend on the detection probability, the phase inside the interferometer, and the choice of the input states. The appropriate parameters for maximized squeezing are obtained. We analyze the influence of losses and confirm that the predicted effects are within reach of current experimental techniques.

Attosecond temporal confinement of interband excitation by intraband motion - Song, Xiaohong; Zuo, Ruixin; Yang, Shidong; Li, Pengcheng; Meier, Torsten; Yang, Weifeng (Optics Express)

Ballistic photocurrents in semiconductor quantum wells caused by the excitation of asymmetric excitons - Duc, Huynh Thanh; Ngo, Cong; Meier, Torsten (Physical Review B)

Oxygen and potassium vacancies in KTP calculated from first principles - Bocchini, Adriana; Neufeld, Sergej; Gerstmann, Uwe; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Improved set up strategies for steel strip straightening machines - Rostek, Tim; Homberg, Werner (AIP Conference Proceedings 2113, 170018)

Numerical Investigation of the Temperature Distribution in PCM-integrated Solar Modules - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Krauter, Stefan; Kenig, Eugeny (CHEMICAL ENGINEERING TRANSACTIONS)

Numerische Untersuchung der Temperaturverteilung in PCM-integrierten Solarmodulen - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Kenig, Eugeny

Entwicklung eines thermischen 1D-Simulationsmodells zur Bestimmung der Temperaturverteilung in Solarmodulen - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Krauter, Stefan; Kenig, Eugeny

Bestimmung von Wärmeverlusten in Haushaltskältegeräten - Paul, Andreas; Moczarski, Lukas; Gieselmann, Mirko; Reineke, Michael; Elsner, Andreas; Baumhögger, Elmar; Sonnenrein, Gerrit; Vrabec, Jadran
Wie jedes technische System unterliegen auch Haushaltskältegeräte einer alterungsbedingten Degeneration, die zu einem Anstieg der Energieaufnahme über die Lebensdauer dieser Geräte führt. Ursache hierfür sind verschiedene Effekte, die in dem vom BMWi geförderten Projekt ALGE untersucht werden. Aus den so gewonnenen Erkenntnissen sollen dann degenerationsbeständigere Haushaltskältegeräte entwickelt werden. Eine wichtige Alterungsursache ist der Anstieg der Wärmeleitfähigkeit des PUR-Schaums der Gehäuseisolierung. Zur Bestimmung dieses Einflusses auf die Energieaufnahme ist die Entwicklung neuer Messmethoden notwendig, die zerstörungsfrei sein und den realen Anwendungsbedingungen möglichst nahekommen sollen. Dazu wurde eine Wärmesenke entwickelt, die den Geräteinnenraum unabhängig vom Kältekreislauf abkühlt. Die Wärmesenke ist als Eiswasserbehälter ausgeführt, sodass die Schmelzenthalpie des Eises die durch die Isolierung in den Geräteinnenraum einfallende Wärme aufnimmt. Durch die Bestimmung der Abtauzeit einer bestimmten Eismenge kann so der alterungsbeeinflusste 𝑘∙𝐴-Wert des Gehäuses von Haushaltskältegeräten bestimmt werden.

Loaded Language: Gun Rights and the Rhetoric of Post-Truth Politics. - Jende, Yvonne Kristin (Deception, Dishonesty, and Duplicity, Interdisziplinäre studentische Konferenz)

Qualitätsoptimierung im mechanischen Fügen durch Einsatz von Mensch-Roboter-Kollaboration - Neumann, Stefan; Meschut, Gerson; Schmatz, Frederik; Flügge, Wilko

Surface Inoculation of Aluminium Powders for Additive Manufacturing Guided by Differential Fast Scanning Calorimetry - Tasche, Lennart; Hoyer, Kay-Peter; Zhuravlev, Evgeny; Grundmeier, Guido; Schaper, Mirko; Keßler, Olaf (The Minerals, Metals & Materials Series)

Influence of the process temperature on the tribological behaviour during bulk forming of high nitrogen steel - Kuball, Clara-Maria; Jung, R; Uhe, Benedikt; Meschut, Gerson; Merklein, Marion

Application of Network Analysis to Flow Systems with Alternating Wave Channels: Part A (Pressure Flows). - Schöppner, Volker; Dörner, M.; Marschik, C.; Roland, W.; Miethlinger, J.; Steinbichler, G. (Polymers)

Orientation in LLDPE Cast Films Manufactured under Different Processing Parameters - Bayazian, Hoda; Schöppner, Volker; Yadegari , Ali; Haddad , Hoda

Bloch oscillations of multidimensional dark soliton wave packets and light bullets - Driben, R; Ma, Xuekai; Schumacher, Stefan; Meier, Torsten (Optics Letters)

Oper und Film. Geschichten einer Beziehung.

Opern für die Leinwand. Erich Wolfgang Korngolds Filmmusik im Hollywood-Melodrama - Ahrens, Stephan (Oper und Film. Geschichten einer Beziehung)

Das Volk lacht auf. Notizen zur DEFA-Komödie - Ahrens, Stephan (Historische Urteilskraft. Magazin des Deutschen Historischen Museums 1)

Julie Delpy: unvermutete Abgründe - Ahrens, Stephan (Filmbulletin, 7)

Ein umstrittener Meister. Nachruf auf den italienischen Opern-, Theater- und Filmregisseur Franco Zeffirelli - Ahrens, Stephan

Geteilte Historische Erfahrung - Ahrens, Stephan (Dschungel (Jungle World))

Die erlösende Kraft des Stars - Ahrens, Stephan (die tageszeitung)

IndieLisboa 2019: Undurchlässige Bilder - Ahrens, Stephan